Labor Assistance in Obtaining Severance Rights at PHI (Industrial Relations Court) - Firda Nawang Wulan; Muhammad Wisnu Raka Pratikno; Rini Eka Agustina; Putri Sari Asih; Khairum Nisa Karuna Putri (Proceeding International Conference Restructuring and Transforming Law, 2022)
The Indonesian state is juridically as a country with the concept of a Welfare State or a welfare state. Welfare State as a form of government policy towards public interests, including labor regulations. In the era of industrialization which coincides with the advancement of science and technology, the level of complexity of industrial relations disputes is getting higher. The assistance provided includes all former PT.X workers in Sukoharjo Regency. The assistance carried out to Ex-Labourers of PT.X aims to defend and fight for the Severance Rights of Hundreds of Ex-Workers of PT.X. Basically, the settlement of Industrial Relations Disputes is settled through the Industrial Relations Court. However, before reaching that stage, it is necessary to make other efforts or alternative stages in the form of: